Aggression: tachykinin is all the rage. - Pavlou, H; Neville, M; Goodwin, S (Cell Press, 2014)
Animals are constantly receiving information about their environment that must be filtered to ensure that they respond in the appropriate manner. New data have revealed how neurons in male Drosophila promote a heightened state of aggression in response to a rival male.